Signal Interference between GPS and Wide Area Augmentation System - Liu Wei (MATEC Web of Conferences, 2015)
With the development of Global Navigation Satellite System (GNSS), multiple constellations broadcasting more signals in the same frequency bands will cause interference effects on the systems. At a minimum, all GNSS signals and services must be compatible. In this paper, a complete methodology for the signal interference assessment is presented. Real simulations accounting for the interference effects were carried out on the L1 band where GPS and Wide Area Augmentation System (WAAS) are sharing the same band. And the results show that the WASS can provide a sound basis for compatibility with GPS.